A literature research on feasible application of mixed working fluid in flexible distributed energy system. (15th October 2017) - Zhang, Ying; Deng, Shuai; Ni, Jiaxin; Zhao, Li; Yang, Xingyang; Li, Minxia
Abstract: Distributed energy system (DES) has received much attention in the world to solve the conflict between energy saving and emission reduction. The cutting-edge DES can provide multi-products for the diversity of user, such as cooling, heating, power and even desalination, through a cascade utilization of energy. Furthermore, a large-scale application of renewable energy has been considered in DES with a good interaction to grid. Thus, a dynamic balance between the supply and demand sides is urgently required to maximize the benefit from DES to end-user. All of these new features are extending the technical boundary of the conventional DES, and pose a challenge to flexible mechanism of DES's operation. This paper provides a guided technological tour on the proposed concept--flexible DES (FDES), through a literature research, in terms of features, definition, and capacity adjustment measures. In particular, one kind of FDES featured by the application of mixed working fluid (MWF) is highlighted as the main object in this paper through a summary on separation and mixing mechanism of MWF. An overview about the typical technologies to access such mechanisms, including T junction, ejector, cyclone and distillation, is presented to demonstrate advances and application potential of FDES. Finally, two representative cases from publications are briefly presented and discussed for existing configurations of FDES and possible application of separation and mixing technologies. The literature works in this paper proved a promising application prospect of the new concept FDES due to its significant performance improvement and flexible adjustment function. Highlights: A new type of flexible distributed energy system is presented. The system is based on thermodynamic cycle featured by separation and mixing of MWF. Recent advances made in key technologies for the FDES is reviewed. Two representative cases and feasibility of the system are analyzed.